Responses of peak oxygen uptake, velocity at lactate treshold and running economy in professional soccer players during several seasons - Krueger, M.; Broich, H.; Sperlich, B.; Mester, J. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Since professional soccer players have to cover distances up to 12 km during a match, endurance performance is one important component of success (di Salvo et al., 2007). VO2peak, velocity at lactate threshold (VLT) and running economy (RE) have been described as major factors accounting for variance in aerobic endurance performance (Midgley et al., 2007). Therefore the aims of this case study were 1) to investigate how VO2peak, VLT and RE vary within and over several seasons in elite soccer players and 2) to discuss possible practical applications. METHODS: VO2peak, VLT and RE of 12 professional and international level soccer players (25 ± 3 yrs, 184 ± 7 cm, 79.8 ± 7.5 kg) were measured during eight time points (i.e. July 2006 [0706]; January [0107] and July 2007 [0707]; January [0108], July [0708], September [0908] and December of 2008 [1208] and May 2009 [0509]) before, during and after three soccer seasons using an incremental treadmill protocol (2.8 m/s,increase 0.4 m/s every 5 min). Capillary blood lactate concentration and VO2 were determined at the end of each stage. RE was defined as VO2 in mL/kg/min at 3.2 m/s. ACSM-criteria for exertion were met in all tests. RESULTS: VO2peak expressed as mL/min/kg was significantly elevated in September 08 when compared to the other time points (57.3 ± 2.5 vs. 55.5 ± 3.4 [0706], 55.6 ± 2.7 [0107], 55.4 ± 3.8 [0707], 55.1 ± 3.0 [0108], 55.3 ± 3.6 [0708], 56.3 ± 4.3 [1208], 54.5 ± 4.3 [0509]; best P = .03). VLT expressed as m/s was also significantly elevated in September 08 when compared to the other time points in the same year (3.29 ± 0.12 vs. 3.24 ± 0.07 [0108], 3.24 ± 0.10 [0708], 3.26 ± 0.09 [1208]; best P = .02) while RE remained unaltered from 0706 to 0509 (best P = .17). CONCLUSION: This study showed: 1) RE is not influenced by pre- or in-season exercise in elite soccer players. 2) VO2peak and VLT elevated from preseason (July 08) to September 08, but declined to December of the same season. This can be explained by an additional endurance block during season preparation, which is no longer possible during the season due to several matches per week. It seems that frequent match play is not sufficient to maintain high levels of VO2peak and VLT during an entire season. We therefore suggest 1) to routinely assess all three endurance relevant parameters in professional soccer players and 2) to implement short conditioning blocks (e.g. high intensity interval training) during the season to maintain a high level of physical fitness.